A haploid diamondback moth (Plutella xylostella L.) genome assembly resolves 31 chromosomes and identifies a diamide resistance mutation. (November 2021) - Ward, C.M.; Perry, K.D.; Baker, G.; Powis, K.; Heckel, D.G.; Baxter, S.W.
Abstract: The diamondback moth, Plutella xylostella (L.), is a highly mobile brassica crop pest with worldwide distribution and can rapidly evolve resistance to insecticides, including group 28 diamides. Reference genomes assembled using Illumina sequencing technology have provided valuable resources to advance our knowledge regarding the biology, origin and movement of diamondback moth, and more recently with its sister species, Plutella australiana . Here we apply a trio binning approach to sequence and annotate a chromosome level reference genome of P. xylostella using PacBio Sequel and Dovetail Hi-C sequencing technology and identify a point mutation that causes resistance to commercial diamides. A P. xylostella population collected from brassica crops in the Lockyer Valley, Australia (LV-R), was reselected for chlorantraniliprole resistance then a single male was crossed to a P. australiana female and a hybrid pupa sequenced. A chromosome level 328 Mb P. xylostella genome was assembled with 98.1% assigned to 30 autosomes and the Z chromosome. The genome was highly complete with 98.4% of BUSCO Insecta genes identified and RNAseq informed protein prediction annotated 19, 002 coding genes. The LV-R strain survived recommended field application doses of chlorantraniliprole, flubendiamide and cyclaniliprole. Some hybrids also survived these doses, indicating significant departure from recessivity, which has not been previously documented for diamides. Diamide chemicals modulate insect Ryanodine Receptors (RyR), disrupting calcium homeostasis, and we identified an amino acid substitution (I4790K) recently reported to cause diamide resistance in a strain from Japan. This chromosome level assembly provides a new resource for insect comparative genomics and highlights the emergence of diamide resistance in Australia. Resistance management plans need to account for the fact that resistance is not completely recessive. Graphical abstract: Image 1 Highlights: Chromosome level assembly of a diamide resistant diamondback moth genome. A trio binning approach resolved a complete haploid genome. Genome annotation predicts 19 thousand genes, including the diamide receptor, RyR. RyR diamide resistance mutation I4790K identified in Australia. Diamide resistance is incompletely recessive.